2021
DOI: 10.1021/acsami.1c05587
|View full text |Cite
|
Sign up to set email alerts
|

DOPO-Decorated Two-Dimensional MXene Nanosheets for Flame-Retardant, Ultraviolet-Protective, and Reinforced Polylactide Composites

Abstract: This study presents a novel and facile strategy for fabricating fire-resistant, ultraviolet (UV)-shielding, and tensileenhanced polylactide (PLA) composites using two-dimensional (2D) MXene (Ti 3 C 2 ) flakes chemically modified with 9,10dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). The thermal and burning performances of PLA composites were demonstrated by the limiting oxygen index, UL-94 test, and cone calorimetry. The UV-shielding and tensile performances were also examined. The results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 51 publications
(107 reference statements)
0
33
0
Order By: Relevance
“…When the addition of these high-performance flame retardants was lower than 5%, the prepared PLA composite reached the UL-94 V-0 level. [65][66][67][68] However, unlike other flame-retardant polymer composites such as polypropylene and polyethylene composites, most of the reported flame-retardant PLA composite showed obvious melt dripping phenomenon. To some extent, the melt dripping of PLA composite can directly affect the UL-94 test result of the PLA composite.…”
Section: Effect Of Biodegradation On the Ul-94 Test Of Pla Compositementioning
confidence: 99%
“…When the addition of these high-performance flame retardants was lower than 5%, the prepared PLA composite reached the UL-94 V-0 level. [65][66][67][68] However, unlike other flame-retardant polymer composites such as polypropylene and polyethylene composites, most of the reported flame-retardant PLA composite showed obvious melt dripping phenomenon. To some extent, the melt dripping of PLA composite can directly affect the UL-94 test result of the PLA composite.…”
Section: Effect Of Biodegradation On the Ul-94 Test Of Pla Compositementioning
confidence: 99%
“…At present, adding flame retardants is considered one of the most common and effective ways to suppress the fire hazards of EP . In recent years, many kinds of flame retardants have been designed to endow EP with flame retardancy. However, most flame retardants have cumbersome synthesis routes, with the main raw materials coming from nonrenewable petrochemicals, and require large amounts of organic solvents to synthesize flame retardants. Therefore, the development of synthesis processes for simple and sustainable flame retardants has become a hot topic.…”
Section: Introductionmentioning
confidence: 99%
“…MXene shows remarkable effectiveness as a multifunctional additive with fascinating physical and chemical properties, which has potential applications in the fields of electromagnetic shielding, smart sensors, catalysis, etc. At the same time, some scholars have gradually paid attention to the thermal stability, high specific surface area, and metal catalytic activity of MXene and believe that it has potential to become an effective flame-retardant filler, which is also conducive to the development of high-performance polymer composites. Gong et al showed that incorporating 1% MXene into the EP matrix can reduce the peak heat release rate (PHRR) and peak smoke release (PSPR) rate of EP by 24.1 and 34.6%, respectively. Meng et al found that phytic acid-modified MXene (P-MXene) would endow EP with a 38.6% and 31.6% drop in PHRR and PSPR, respectively.…”
Section: Introductionmentioning
confidence: 99%